2020
DOI: 10.3390/ijerph17103501
|View full text |Cite
|
Sign up to set email alerts
|

Lung Diffusion in a 14-Day Swimming Altitude Training Camp at 1850 Meters

Abstract: Swimming exercise at sea level causes a transient decrease in lung diffusing capacity for carbon monoxide (DLCO). The exposure to hypobaric hypoxia can affect lung gas exchange, and hypoxic pulmonary vasoconstriction may elicit pulmonary oedema. The purpose of this study is to evaluate whether there are changes in DLCO during a 14-day altitude training camp (1850 m) in elite swimmers and the acute effects of a combined training session of swimming in moderate hypoxia and 44-min cycling in acute normobaric seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A small amount of cortisol can cause euphoria, and too much cortisol can cause poor thinking and irritability [36]. Numerous studies have shown that long-term subalpine training can maintain cortisol at a high level [12,13]. In this study, after long-term subalpine training, the time-oriented effects all had significant changes and were significantly higher compared to the pre-subalpine period, with male athletes showing a significant increase at month 4 and female athletes showing a significant increase at month 2 versus months 4 and 6, with female athletes averaging 100 nmol/L higher than male athletes.…”
Section: Effects Of Subalpine Training On Cortisol Blood Urea and Cre...mentioning
confidence: 99%
See 2 more Smart Citations
“…A small amount of cortisol can cause euphoria, and too much cortisol can cause poor thinking and irritability [36]. Numerous studies have shown that long-term subalpine training can maintain cortisol at a high level [12,13]. In this study, after long-term subalpine training, the time-oriented effects all had significant changes and were significantly higher compared to the pre-subalpine period, with male athletes showing a significant increase at month 4 and female athletes showing a significant increase at month 2 versus months 4 and 6, with female athletes averaging 100 nmol/L higher than male athletes.…”
Section: Effects Of Subalpine Training On Cortisol Blood Urea and Cre...mentioning
confidence: 99%
“…Creatine kinase is associated with skeletal muscle energy metabolism and serum CK is commonly used to assess the intensity of loading, reflecting the degree of fatigue and damage to skeletal muscle [42]. Studies have shown that athletes' serum CK is up-regulated in the early stage of sub-altitude training [13]. The main reasons are: exercise stretch and increase metabolites increase the permeability of muscle cells, increased catecholamines, and tissue cell damage.…”
Section: Effects Of Subalpine Training On Cortisol Blood Urea and Cre...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the training load monitoring results, the lack of HIT training may have contributed to the lack of cardiorespiratory and physiological stimulation. In addition to no changes in physiological indicators, training at 1550 m may not suffer any change in lung diffusing, which was proved in 1800 m swimming training [38]. A detailed examination applied in a meta-analysis about altitude training reveals a lag in the change in maximal oxygen uptake after altitude training.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have confirmed that altitude or hypoxic training can increase athletes’ blood volume and hemoglobin (Hb) levels ( Bonne et al, 2014 ; Tannheimer et al, 2010 ; Wachsmuth et al, 2013 ), improve the body’s ability to buffer acids such as blood lactic acid (BLA) ( Ramos-Campo et al, 2018 ; Shaw et al, 2020 ), and increase the number of capillaries and mitochondria in skeletal muscle ( Hoppeler et al, 2003 ; Vogt et al, 2001 ). At present, studies concerning the effects of plateau or hypoxic training on athletes’ physical functional status and athletic ability have mainly focused on physical events that occur during the summer, such as rowing, swimming, cycling, middle-distance running, boxing, and sparring ( Gao, Gao & Meng, 2018 ; Garcia et al, 2020 ; Millet & Brocherie, 2020 ). Athletes in these events have improved their physical functional and athletic ability through plateau or hypoxic training and have achieved excellent athletic results in major competitions at home and abroad ( Arezzolo et al, 2020 ; Gao et al, 2019 ; Gao, Gao & Meng, 2018 ; Viscor et al, 2018 ; Zhao, Li & Lu, 2008 ).…”
Section: Introductionmentioning
confidence: 99%